PENGANTAR PSIKOLOGI PERKEMBANGAN ANAK - Harahap, Najwa Nadhira (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2023)
Introduction to child developmental psychology is a field of study that studies the physical, cognitive, social and emotional development of children from infancy to adolescence. An introduction to child developmental psychology involves understanding how children grow and develop over time. The study begins with development theories that have been developed by experts, such as Jean Piaget, Erik Erikson, and Lev Vygotsky. These theories provide a framework for understanding children's developmental stages, including their thinking abilities, emotions, morals, and social relationships. The importance of studying child developmental psychology is to gain a better understanding of how children grow and develop. This can help parents, educators and health practitioners provide appropriate attention and support children in achieving their optimal potential.